Pengaruh Media Exposure, Kinerja Lingkungan, Profitabilitas, terhadap Pengungkapan Emisi Karbon dengan Varaibel Pemoderasi Dewan Komisaris Independen - Razqouli Dimaszocarli Siregar (AKUNTANSI 45, 2026)
The significance of revealing carbon emissions as part of company sustainability policies has grown due to global climate change. Indonesia still reports carbon emissions in an ambiguous way, though. With the help of the percentage of independent commissioners, this study will look at how media exposure, environmental performance, and profitability affect the disclosure of carbon emissions in mining companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2024. This study uses both an explanatory strategy and a quantitative technique. Secondary data came from yearly reports, sustainability reports, and pertinent media coverage. A dummy variable is used to quantify media exposure, PROPER ratings are used to measure environmental performance, and ROA is used to measure profitability. By dividing the number of independent commissioners by the total number of commissioners, the percentage of independent commissioners the moderating variable is found. The GRI Index 305 checklist is used to assess the content analysis, carbon emission disclosure, and dependent variable. It is anticipated that this study will shed further light on the elements that encourage or discourage businesses from revealing their carbon emissions and provide useful recommendations for investors, regulators, and businesses looking to encourage openness and environmentally responsible practices.